Reduced Folate Carrier: an Entry Receptor for a Novel Feline Leukemia Virus Variant - Miyake, Ariko; Kawasaki, Junna; Ngo, Ha; Makundi, Isaac; Muto, Yutaro; Khan, Arshad H.; Smith, Desmond J.; Nishigaki, Kazuo (Journal of virology, 2019)
Feline leukemia virus (FeLV) is a member of the genus Gammaretrovirus , which causes malignant diseases in cats. The most prevalent FeLV among cats is FeLV subgroup A (FeLV-A), and specific binding of FeLV-A Env to its viral receptor, thiamine transporter feTHTR1, is the first step of infection. In infected cats, novel variants of FeLV with altered receptor specificity for viral entry have emerged by mutation or recombination of the env gene. A novel FeLV variant arose from a subtle mutation of FeLV-A Env, which altered the specific interaction of the virus with its receptor. RFC, a folate transporter, is a potential receptor for the novel FeLV variant. The perturbation of specific retrovirus-receptor interactions under selective pressure by the host results in the emergence of novel viruses. Feline leukemia virus (FeLV) is horizontally transmitted among cats and causes a variety of hematopoietic disorders. Five subgroups of FeLV, A to D and T, each with distinct receptor usages, have been described. Recently, we identified a new FeLV Env (TG35-2) gene from a pseudotyped virus that does not belong to any known subgroup. FeLV-A is the primary virus from which other subgroups have emerged via mutation or recombination of the subgroup A env gene. Retrovirus entry into cells is mediated by the interaction of envelope protein (Env) with specific cell surface receptors. Here, phenotypic screening of a human/hamster radiation hybrid panel identified SLC19A1, a feline reduced folate carrier (RFC) and potential receptor for TG35-2-phenotypic virus. RFC is a multipass transmembrane protein. Feline and human RFC cDNAs conferred susceptibility to TG35-2-pseudotyped virus when introduced into nonpermissive cells but did not render these cells permissive to other FeLV subgroups or feline endogenous retrovirus. Moreover, human cells with genomic deletion of RFC were nonpermissive for TG35-2-pseudotyped virus infection, but the introduction of feline and human cDNAs rendered them permissive. Mutation analysis of FeLV Env demonstrated that amino acid substitutions within variable region A altered the specificity of the Env-receptor interaction. We isolated and reconstructed the full-length infectious TG35-2-phenotypic provirus from a naturally FeLV-infected cat, from which the FeLV Env (TG35-2) gene was previously isolated, and compared the replication of the virus in hematopoietic cell lines with that of FeLV-A 61E by measuring the viral RNA copy numbers. These results provide a tool for further investigation of FeLV infectious disease. IMPORTANCE Feline leukemia virus (FeLV) is a member of the genus Gammaretrovirus , which causes malignant diseases in cats. The most prevalent FeLV among cats is FeLV subgroup A (FeLV-A), and specific binding of FeLV-A Env to its viral receptor, thiamine transporter feTHTR1, is the first step of infection. In infected cats, novel variants of FeLV with altered receptor specificity for viral entry have emerged by mutation or recombination of the env gene. A novel FeLV variant arose from a subtle mutation of FeLV-A Env, which altered the specific interaction of the virus with its receptor. RFC, a folate transporter, is a potential receptor for the novel FeLV variant. The perturbation of specific retrovirus-receptor interactions under selective pressure by the host results in the emergence of novel viruses.